SISTEM INFORMASI PENCATATAN DAN PENGONTROLAN IBU HAMIL BERBASIS ANDROID (STUDI KASUS DESA KOLAI KABUPATEN ENREKANG) - Ririn Syaputri; Mustikasari (AGENTS: Journal of Artificial Intelligence and Data Science, 2021)
The Maternal and Child Health Book (KIA) is the administrative book for pregnant women and midwives whenever control the health of the fetus during pregnancy until giving birth. The KIA book contains records of pregnant women as well as various information on how to maintain and care for the health of mothers and children. Therefore the KIA handbook is very important and must always be considered because it is an administrative completeness during control. It is also a guide for pregnant women in maintaining their health after giving birth during the postpartum period. In Kolai Village, pregnant women use KIA handbooks, so they are not very effective because easily scattered or even lost. Thus, this research can provide an effective solution, with an Android-based information system for recording and controlling pregnant women as a substitute for manual bookkeeping for pregnant women. The method used in system design is a prototype method with black box testing which is equipped with implementation as a system test and questionnaire with the results of the questionnaire being processed quantitatively. The results are in the form of recording and controlling pregnant women as an information system which is the main feature of the application.